Taking random values will not do

Algebra Level 3

x + 1 y z = 1 5 y + 1 x z = 1 15 z + 1 x y = 1 3 \large{\begin{aligned}x+\dfrac{1}{yz} &= \dfrac{1}{5}\\ y+\dfrac{1}{xz} &= -\dfrac{1}{15}\\ z+\dfrac{1}{xy} & =\dfrac{1}{3} \end{aligned}} If x , y x,y and z z are real numbers which satisfy the given equations above, find z y z x \dfrac{z-y}{z-x} .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Atul Shivam
Jan 19, 2016

the above three equation gives x y z + 1 = y z 5 = x z 15 = x y 3 xyz+1=\frac{yz}{5}= \frac{-xz}{15}= \frac{xy}{3}

now from above equation 3 z = 5 x , 3 y = x , z = 5 y 3z=5x,3y=-x,-z=5y

let's see what we have to find, it is z y z x \frac{z-y}{z-x} so if we convert x , y x,y in the form of z z than it will be quite helpful,

now x = 3 5 z x= \frac{3}{5}z

y = z 5 y= \frac{-z}{5}

So at last z y z x = z ( 1 + 1 5 ) z ( 1 3 5 ) = 3 \frac{z-y}{z-x}= \frac{z(1+\frac{1}{5})}{z(1-\frac{3}{5})}=3

so the correct answer is 3 \boxed{3}

Rishabh Jain
Jan 19, 2016

x y z + 1 y z = 1 5 , x y z + 1 x z = 1 15 , x y z + 1 x y = 1 3 \dfrac{xyz+1}{yz}=\dfrac{1}{5}, \dfrac{xyz+1}{xz}=\dfrac{-1}{15}, \dfrac{xyz+1}{xy}=\dfrac{1}{3} y z 5 = x z 15 = x y 3 \Rightarrow \dfrac{yz}{5}=\dfrac{-xz}{15}=\dfrac{xy}{3} x y = 3 a n d z y = 5 \Rightarrow \dfrac{x}{y}=-3 ~and~ \dfrac{z}{y}=-5 z y z x = 5 y y 5 y + 3 y = 3 \Rightarrow \dfrac{z-y}{z-x}=\dfrac{-5y-y}{-5y+3y}=\Large\color{forestgreen}{3}

Prasath M
Jan 22, 2016

i have done the sum algebrically correct.But logically Idon't agree with the second equation, because x,y,z are real numbers, the equivalent value should not be negative.

Youssef Ali
Jan 19, 2016

By subtracting equations:

(3)-(2)

z+ 1 x y \frac {1}{xy} -y- 1 x z \frac {1}{xz} = 1 3 \frac {1}{3} - 1 15 \frac {-1}{15}

z-y+ z y x y z \frac {z-y}{xyz} = 6 15 \frac {6}{15}

By taking (z-y) as a common factor:

(z-y)(1+ 1 x y z ) \frac {1}{xyz}) )= 6 15 \frac {6}{15} ...*

Then we subtract (3)-(1):

z+ 1 x y \frac {1}{xy} -x- 1 y z \frac {1}{yz} = 1 3 \frac {1}{3} - 1 5 \frac {1}{5}

z-x+ z x x y z \frac {z-x}{xyz} = 2 15 \frac {2}{15}

By taking (z-x) as a common factor:

(z-x)(1+ 1 x y z ) \frac {1}{xyz}) )= 2 15 \frac {2}{15} ...**

Then:

\frac {*}{**}

( z y ) ( z x ) \frac {(z-y)}{(z-x)} =3

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...